(3GdQO Ydi GdRfOjb GHf GdebaYs - (3GdbGSe Hf EHQGgje Hf eSdes
(3ChdgG (B:s
(3CMeO Gddg NGdb cd eYHhO hGdeSJhLH ddMeO s
(3BNQgG (B:s
(3EPG cGf eG NdG Refg ZjQ eSJfcQ hGdMeO ddg QH GdYGdejf hUdi Gddg Ydi eMeO hCgdg GdWGgQjf Je HYhf Gddg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3GdfSNI HgG MhGTs
(3fSNI KGfjIs
(3eUOQ GbJfGA GdCUd (B:s
(3GdEeHQhRjGfG (B(131 C) s
Keywords: (3GdehSjbi hGdZfGAs